Market of sanatorium services in Kazakhstan: condition and perspectives (Journal of Economic Research & Business Administration, 2016)
This article focuses on the development of market health and health services in Kazakhstan. Analyzed the situation in Kazakhstan, describes the main actors of the market of sanatorium services identified constraints to the development of market health and health services in Kazakhstan. As the main problem is indicated by the absence of a holistic concept and the imperfection of the legislative framework in the field of health and health services. An analysis of the sources and research, practical recommendations for the development of market health and health services, the implementation of which would improve the situation in the market of health and health services. The author concludes that the unprecedented role of skills development on the market of health and health services. In conclusion emphasizes that the further growth of the market of sanatorium services is impossible without a welleducated and trained personnel. It is on the development of the market of sanatorium services will largely depend on the level of public health.
Keywords: sanatorium system; the market of sanatorium services; competition; competitiveness; training.